An assignment of humanitarian aid applied to the care of populations affected by natural disasters - De La Cruz Cuadros, Lucy Haydeé (2020)
The frequency and impact of natural disasters are increasing, which worries affected countries, especially those where populations are most vulnerable. In Peru, vulnerability to phenomena increases due to actions of the populations that locate their homes on the banks of the active rivers, in the temporarily inactive river beds, in the streams where debris, rocks, vegetation. The Chosica district is no stranger to this situation, becoming a place with high vulnerability. During the El Niño Phenomenon of 2017, Chosica suffered the consequences of heavy flooding of the Rímac River. Given this, this study seeks to mitigate the impact of future floods in the Chosica District, determining the allocation of centralized aid by responsible government entities, prioritizing the residents according to the severity of the impact suffered and providing that support with the greatest effectiveness. For this, tools and models of Operational Research are used.